LC-MS/MS Quantification of Tramadol and Gabapentin Utilizing Solid Phase Extraction - Pappula Nagaraju; Balaji Kodali; Peda Varma Datla; Surya Prakasarao Kovvasu (International Journal of Analytical Chemistry)
An accurate, highly sensitive, and precise method for quantitative analysis of tramadol (TMD) and gabapentin (GBP) by high performance liquid chromatography and tandem mass spectrometry in human plasma was proposed and validated successfully using venlafaxine and pregabalin as internal standards (ISTDs), respectively. An aliquot of 200 μL of plasma was mixed with internal standard dilution and extraction was performed by using solid phase extraction (SPE) technique. Peak resolution was achieved on Phenomenex PFP column (50×4.6 mm, 2.6 μm). The total analytical run time was 3.8 min. Both analytes were monitored using multiple reaction monitoring (MRM) scan and the mass spectrometer was operated in positive polarity mode. The method was validated for specificity, sensitivity, precision, accuracy, and other analytical parameters. The results found were satisfactory over the linear calibration range of 1-500 ng/mL and 10-6000 ng/mL for TMD and GBP, respectively. The developed method can be ready to use by scientific community for quantification of analytes in plasma samples from various clinical studies of different dose strengths.